Pendidikan Islam dalam Era Revolusi Industri 4.0 - Priyanto, Adun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The challenges facing the world of education are becoming increasingly complex, education is said to adjust to the existence of an era of technological progress, technology integration. This means that the modernization of Islamic education based on character education becomes a necessity to create education in accordance with the needs of the millennial era. This study aims to determine the problems of Islamic education that are happening and how the challenges of Islamic education in the future. Then how is the solution for the world of Islamic education to be able to compete and even become a reference in the implementation of education in Indonesia. The research method uses literature study by collecting data from documentation using descriptive-analysis method. The results of the study can be concluded, Islamic education transformation is greatly required to gain solutions from the arising crisis and problems. Strengthening the Islamic educational institutions also requires more attention, including strengthening the Islamic educational management, Islamic educational leadership, and educational policy reform which is intended to create an intact generation as well as excellent and competitive human resources with creativity, innovations, character, independence, nationality, and religiously in facing Era 4.0 where humans are expected to be fast, accurate, effective, and efficient.Keywords. Islamic Educations; The Industrial Revolution Era 4.0